Tertiary Lymphoid Structures and Chemokine Landscape in Virus-Positive and Virus-Negative Merkel Cell Carcinoma - Nakamura, Motoki; Magara, Tetsuya; Kano, Shinji; Matsubara, Akihiro; Kato, Hiroshi; Morita, Akimichi (Frontiers in Oncology, 2022)
Tertiary lymphoid structures (TLSs) are used as biomarkers in many cancers for predicting the prognosis and assessing the response to immunotherapy. In Merkel cell carcinoma (MCC), TLSs have only been examined in MCPyV-positive cases. Here, we examined the prognostic value of the presence or absence of TLSs in 61 patients with MCC, including MCPyV-positive and MCPyV-negative cases. TLS-positive samples had a significantly better prognosis than TLS-negative samples. MCPyV-positive samples had a good prognosis with or without TLSs, and MCPyV-negative/TLS-positive samples had a similarly good prognosis as MCPyV-positive samples. Only MCPyV-negative/TLS-negative samples had a significantly poor prognosis. All cases with spontaneous regression were MCPyV-positive/TLS-positive. We also performed a comprehensive analysis of the chemokines associated with TLS formation using next-generation sequencing (NGS). The RNA sequencing results revealed 5 chemokine genes, CCL5, CCR2, CCR7, CXCL9, and CXCL13, with significantly high expression in TLS-positive samples compared with TLS-negative samples in both MCPyV-positive and MCPyV-negative samples. Only 2 chemokine genes, CXCL10 and CX3CR1, had significantly different expression levels in the presence or absence of MCPyV infection in TLS-negative samples. In conclusion, the presence of TLSs can be a potential prognostic marker even in cohorts that include MCPyV-negative cases. Chemokine profiles may help to understand the tumor microenvironment in patients with MCPyV-positive and MCPyV-negative MCC.